Variability of black carbon mass concentrations, sub-micrometer particle number concentrations and size distributions: results of the German Ultrafine Aerosol Network ranging from city street to High Alpine locations. (1st April 2019) - Sun, J.; Birmili, W.; Hermann, M.; Tuch, T.; Weinhold, K.; Spindler, G.; Schladitz, A.; Bastian, S.; Löschau, G.; Cyrys, J.; Gu, J.; Flentje, H.; et al.
Abstract: This work reports the first statistical analysis of multi-annual data on tropospheric aerosols from the German Ultrafine Aerosol Network (GUAN). Compared to other networks worldwide, GUAN with 17 measurement locations has the most sites equipped with particle number size distribution (PNSD) and equivalent black carbon (eBC) instruments and the most site categories in Germany ranging from city street/roadside to High Alpine. As we know, the variations of eBC and particle number concentration (PNC) are influenced by several factors such as source, transformation, transport and deposition. The dominant controlling factor for different pollutant parameters might be varied, leading to the different spatio-temporal variations among the measured parameters. Currently, a study of spatio-temporal variations of PNSD and eBC considering the influences of both site categories and spatial scale is still missing. Based on the multi-site dataset of GUAN, the goal of this study is to investigate how pollutant parameters may interfere with spatial characteristics and site categories. Highlights: Pollutant parameters show various connections with spatial scale and site category. Lower spatial correlation of PNC and eBC is observed for lager spatial distance. eBC connects sites with similar influence of anthropogenic sources. N [10-30] are mainly driven by local source. N [200-800] connects sites located at same geographical area.